The influence of palm fronds ash (PA) on some physical properties of polypropylene (PP). - Nadhim A. Abdullah; Ahmed J. Mohammed; Ziad T. Falik; Ahmad J.H. Almaliky; Ibrahim K. Ibrahim (Genius Journals, 2023)
The base material was polypropylene (PP), and the filler was palm frond ash (PFA) in weight percentages of( 1%, 2%, 3%, 4%, 5%, 6%, 7.5%, and 10%), with an equivalent particle size of (75 μm). For determining the mechanical properties of the mixes (the proportionate limit), measure a variety of variables of the new material (the base material and the filler addition), including stress at yield, stress at break, elongation, Young's modules, and the limit of proportion to the polymer with fillers. The practical outcomes of this study demonstrated that adding palm frond ash to the polymer decreases the gaps between the polymeric chains, reflecting the polymer's high pressure tolerance, that the degree of homogeneity between the polymer and fillings is high, and that increasing the percentage of additives increases the character of the polymer. The results indicated that the tensile strength behavior is effective at a percentage (1%) of the addition, then declines with a very slight percentage rise in the amount of the additive. The hardness of the manufactured samples was at a percentage (1%). The Young's coefficient is low with its percentage added at 2% because palm frond ash as filler impacts the properties of polypropylene; this demonstrates the flexibility of the polymer grafted with palm frond ash and the expansion of the polymer's range of applications
Keywords: Polypropylene; palm frond ash; thermal conductivity